Physical, thermal and micro-surface characteristics of PG76 binder incorporated with liquid chemical WMA additive. (22nd February 2021) - Rahmad, Suzielah; Atmaja P. Rosyidi, Sri; Aziz Memon, Naeem; Haji Badri, Khairiah; Widyatmoko, Iswandaru; Kamil Arshad, Ahmad; Koting, Suhana; Izzi Md Yusoff, Nur; Rosli Hainin, Mohd
Highlights: The incorporation of Rediset into PG76 lowers the Ea. Rediset improves the adhesiveness property of the blending. Rediset is not susceptible to high temperatures. The typical bee-structures were observed on the surface of all the binders. Abstract: The effect of different percentage of a warm-mix asphalt (WMA) additive with the proprietary name Rediset LQ 1106, on the properties of a performance grade polymer modified binder (PMB), PG76 was studied. The rotational viscosity (RV) test was conducted to assess the mixing efficiency of each blending by Rediset against the asphalt binder. The behavior of adhesion and stripping of the blends were also witnessed through Vialit Adhesion and Boiling Water tests. The concept of atomic force microscopy (AFM) tested to evaluate the morphology characteristics of the blends comprehensively. The results illustrated that Rediset reduced the viscosity and modified physical characteristics of the blends. Vialit adhesion and boiling water tests indicated that the adhesion properties of all blends withstand the impact force but lessen when in boiling water. Thermogravimetry analysis via TGA exhibited that inclusion of WMA in PMB has no significant effect in the thermal stability of the new binders as they are stable beyond their mixing and compaction temperature. The decomposition occurred in three stages at temperature range of 360 to 500 °C for all samples. The AFM analysis envisioned the changes in morphology of all samples added with Rediset.